Resilience and protective factors among people with a history of child maltreatment: a systematic review - Meng, Xiangfei; Fleury, Marie-Josee; Xiang, Yu-Tao; Li, Muzi; D’Arcy, Carl (Social Psychiatry and Psychiatric Epidemiology, 2018)
Purpose To provide an overview of resilience and protective factors associated with a better life following child maltreatment exposure, to compare protective factors across specific subtypes of maltreatment, and to explore existing issues in the current state of the literature. Methods Electronic databases and grey literature up to October 2017 were systematically searched for English language with observational study designs for the research on resilience and childhood maltreatment. Systematic review and qualitative approaches were used to synthesize the results. Study quality and heterogeneity were also examined. Results Initial screening of titles and abstracts resulted in 247 papers being reviewed. A total of 85 articles met eligibility criteria of this review. Most of these studies had low or middle study quality. There were two subgroups of studies reviewed: (1) 11 studies examined whether resilience protected against the negative consequence of childhood maltreatment, and, (2) 75 studies explored what protective factor was associated with a kind of adaptive functioning. Although the conceptualization of resilience significantly varied from study to study, protective factors associated with resilience at individual, familial, and societal levels reduced the likelihood of negative consequences of childhood maltreatment. Negative consequences following childhood maltreatment can be prevented or moderated if protective factors are provided in time. Future research needs to address the conceptualization issue of resilience. Conclusions Public and population mental health preventions should focus on early childhood and apply preventive strategies as early as possible. Cost-effective studies should be considered in the evaluation of resilience prevention program.